Intraoperative Three-dimensional Imaging of Ventricular Septal Defects in Children Using Epicardial Echocardiography: A Novel Approach - Pillai, Manjusha N.; Suneel, Puthuvassery Raman; Menon, Sabarinath; Unnikrishnan, Koniparambil Papu; Baruah, Sudip Dutta; Mathew, Thomas; Lovhale, Sriram Pravin; Dharan, Baiju S. (Journal of cardiothoracic and vascular anesthesia, 2021)
To assess the feasibility and accuracy of intraoperative three-dimensional (3D) epicardial en face images of ventricular septal defects (VSD) in children using the 3D transesophageal echocardiography (TEE) probe as an epicardial probe. This was a prospective nonrandomized blinded observational study. The study was conducted at a single tertiary cardiac care center. Fifty pediatric patients, weighing between 5.0 kg and 20 kg, who were scheduled for elective surgical closure of their VSDs, prospectively were recruited for this study. Epicardial 3D images were acquired using the full-volume mode. VSD location and size were determined from the 3D data sets using multiplanar reconstruction mode (QLAB 9) by a blinded investigator. The accuracy in terms of location and size was compared with surgical findings. In 50 study subjects, 54 VSDs were located by epicardial 3D echocardiography (3DE): 12 perimembranous, 17 inlet, eight muscular, 15 malaligned, and two outlet. Average image acquisition time was 4.96 (±1.47) minutes. Average image reconstruction time was 6.18 (±1.93) minutes. Good en face views of the VSD could be rendered in all patients (100% feasibility). The highest image quality was for perimembranous and malaligned VSDs. The location of VSD by 3DE corresponded precisely with surgical findings (100% accuracy). With linear regression analysis, excellent correlation was observed between the diameters measured by surgery and that measured by 3DE from the right ventricle side (r2 = 0.97, p < 0.001). The authors’ study demonstrated that diagnostic quality 3D en face images of VSD can be obtained intraoperatively using 3D epicardial echocardiography. The short acquisition and reconstruction times make this technique clinically applicable.